Evidence-based scientific policy advice - Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2014)
While policy measures affect the welfare of nations, the practice of policy advice is determined by complex rules. Evidence-based scientific policy advice gives weight to hard empirical facts and restrictions. The lecture discusses challenges and conditions for success and provides suggestions to improve the implementation of such a strategy
Keywords: A11; B4; J48; 330; role of economists; methodology of policy advice; labor reform policies